EFFECT OF HAEMODIALYSIS AND FREQUENCY OF DIALYSIS SESSIONS ON SERUM LIPIDS AND BIOCHEMICAL PROFILE IN PATIENTS WITH CHRONIC KIDNEY DISEASE - Tauqeer, Shazi; Naz, Raisa; Kazmi, Nasir Hussain Shah; Ayub, Muhammad (Pakistan Journal of Physiology, 2018)
Background: Different phenomenon such as loss or accumulation of various substances and dysregulation or alteration in number of metabolic pathways are responsible for aetiology and pathogenesis of chronic changes in chronic kidney disease (CKD). Haemodialysis or renal replacement therapy (RRT) does not correct the dyslipidemia of uraemia but may modify it. The objective of this study was to see the effects of haemodialysis and frequency of dialysis sessions on dyslipidemia and various biochemical markers in patients with CKD. Methods: This was a hospital based cross-sectional observational study conducted in Dialysis Unit of Ayub Teaching Hospital, Abbottabad. In our study renal functions and lipid profile of 30 healthy subjects as control group were compared with 56 cases of CKD undergoing haemodialysis with a frequency of 1, 4, 8, or 12 per moth. Serum lipid profile, renal function tests, serum and urinary albumin was estimated for both the groups. They were further analysed for serum markers before dialysis (pre-HD) and post dialysis, six months (post-HD). Statistical analysis was performed using SPSS-17. Results: Thirty (54%) subjects were males and 26 (46%) were females. The mean age of the patients was 45.48±14.78 years as against mean age of controls (46.78±13.95 years). Urea and creatinine were raised, and anaemia, hypocalcemia, hypoalbuminemia, hyponatremia, and hyperkalemia were observed. A significant elevation in serum total cholesterol, triglycerides, LDL and VLDL-C was seen. There was a reduction in HDL-C in pre-dialysis patients compared to controls. The difference between pre-HD and post-HD groups was unremarkable except for the serum potassium, chloride, urea, creatinine, total cholesterol, triglycerides and HDL-C. The effect of frequency of dialysis sessions was also not statistically significant. Conclusion: Regular treatment with dialysis may partially compensate for loss of renal function and decrease the accumulation of toxic metabolites, but cannot revert the overall physiological deficit. Pak J Physiol 2018;14(1):3–6